Attention vs. accessibility: the role of different cue types for non-canonical sentence production in German - Dolscheid, Sarah; Penke, Martina (Frontiers in Language Sciences, 2023)
There is evidence of close links between the allocation of attention and the production of language. For instance, while speakers commonly produce active sentences when they describe an event with an agent acting on a patient, this preference can shift once the patient is in the spotlight of attention (e.g., by means of a brief attentional cue preceding the patient). In this case, speakers are more prone to produce non-canonical sentences such as passives. Critically, however, whereas attentional cueing is particularly effective for speakers of English, it has proven less effective for speakers of languages like German that differ from English in terms of case-marking and word order flexibility. This observation begs the question of how German speakers respond to alternative cue types that differ in the conceptual and lexical information they provide. In the current study, we address this question by directly comparing the effect of different cue types on sentence production. German-speaking participants were asked to describe transitive event scenes while their eye gaze was monitored via eye tracking. Prior to scene onset, participants saw one of three different cue types: a short attentional cue preceding the patient character, a long attentional cue, or a centrally presented pre-view of the patient (referential cue). Our results demonstrate that different cue types led to differences in speakers' propensity to produce passives. Critically, referential cueing was more effective than attentional cueing in increasing German speakers' rate of passive production, contra to what has previously been reported for English speakers. At the same time, the cues resulted in different viewing behavior, demonstrating that an increase in visual attention does not necessarily go hand in hand with an increase in passivization. Consequently, our findings show that a direct link between the allocation of attention and speakers' structural choices may not always be licensed.